Surgical site infections in Slovenian acute care hospitals: Surveillance results, 2013-2016 - Klavs Irena; Kustec Tanja; Serdt Mojca; Kolman Jana (Sciendo, 2018)
The objective was to present the results of the Slovenian National surgical site infections (SSIs) surveillance system from 2013 to 2016 and to compare them to the reference data for the European Union (EU) and European Economic Area (EEA) countries.